ANALISIS KESALAHAN BERBAHASA DALAM CERPEN SISWA KELAS IX SMP SWASTA SALSA PERCUT - Achmad Yuhdi; Julailanajmi Hasiholanda Tanjung (FKIP, Universitas Palangka Raya, 2023)
This study aims to provide knowledge and explain spelling aspects related to language errors in short stories for class IX students of Salsa Percut Private Middle School which have not been discussed in previous research. The method used is descriptive qualitative method. The analysis in this study is based on the fifth edition of Enhanced Indonesian Spelling (EYD) which was inaugurated on August 16, 2022. Based on the data collected, there are a total of 20 findings of language errors in short stories. Aspects seen in spelling errors, namely the use of capital letters, the use of affixed words, namely: prefixes (prefixes), suffixes (endings), infixes (insertions) and confixes (combined prefixes and suffixes), use of punctuation marks in student short stories. The number of internal errors found in the students' short stories was as follows: 6 capital letter errors, 3 affix words: 6 prefixes, 1 suffix, 0 infix, 3 prepositions, and 3 confix, 4 punctuation errors. These findings were collected in short stories by junior high school students in class IX.